Lupus enteritis: clinical characteristics and predictive factors for recurrence. (May 2015) - Koo, B S; Hong, S; Kim, Y J; Kim, Y-G; Lee, C-K; Yoo, B
Objectives: To compare the clinical characteristics of lupus enteritis (LE) and non-enteric lupus (non-LE) patients and identify predictors of LE recurrence. Methods: We retrospectively reviewed the medical records of 62 systemic lupus erythematosus (SLE) patients in a tertiary hospital who experienced enteric symptoms and underwent abdominal computed tomography scanning between January 1997 and December 2013. We compared the clinical characteristics between LE and non-LE patients and between recurrent LE and non-recurrent LE cases. Results: Out of 62 SLE patients with enteric symptoms, 46 cases (74%) were compatible with LE based on computed tomography findings. The C4 level was decreased in the LE group compared with the non-LE group (9.0 ± 5.6 vs . 12.3 ± 6.2, p = 0.032). Recurrence of LE was observed in 14 patients (28%). Initial involvement at the colon (79% vs . 41%, p = 0.026) and bladder with/without the ureter was more common in the recurrent group (57% vs . 25%, p = 0.048). By multivariate analysis, the hazard ratios of variables associated with recurrence were 4.689 for colon involvement (95% confidence interval: 1.245–17.659, p = 0.0220] and 5.468 for cystitis with/without ureteritis (95% confidence interval: 1.629–18.360, p = 0.006). Conclusion: Colon and urinary tract involvement in LE patients may be associated with the recurrence of LE.